CD4+ T cell subsets in adult allergic rhinitis patients attending Hospital Universiti Sains Malaysia - Sani, Mastura Md (2018)
Memory T cells exert effector function or generate effector cells in response to antigen. The proportions of CD4+ T cell subsets especially memory cells in allergic rhinitis (AR) patients sensitized to common allergens of house dust mites (HDMs) and shellfish have not been extensively studied. This study aimed to compare the mean percentages and absolute counts of CD4+ memory T cell subsets between: (i) non-allergic controls and AR patients; (ii) mild AR patients and moderate-severe AR patients. In addition, sensitization to common allergens, symptom severity scores, and mean absolute counts of leukocyte subsets were also determined. Fifty non-allergic controls and 100 AR patients diagnosed by physicians were recruited in this study. However, only 33 non-allergic controls were included in the analyses as others were excluded due to sensitization to the common allergens (Dermatophagoides farinae (Der f), crab and shrimp) as measured by plasma specific IgE tests. Stratified analyses were done based on two different definitions of AR patients , i.e. (i) non IgE-mediated AR patients; and (ii) IgE-mediated AR patients. Flow cytometry was used to determine the percentage of CD4+ naïve (TN; CD45RA+ CCR7+), central memory (TCM; CD45RA- CCR7+), effector memory (TEM; CD45RA- CCR7-) and terminally differentiated effector memory (TEMRA; CD45RA+ CCR7-) T cells from the peripheral blood. The absolute counts of CD4+ T cell subsets were obtained by dual platform methods from flow cytometer and hematology analyzer. It was observed that AR patients sensitized to common allergens (Dermatophagoides pteronyssinus, Der f, crab and shrimp) measured were predominantly sensitized to HDMs as compared to shellfish allergens. Moderatesevere AR patients had higher nasal and non-nasal symptom scores and reduced quality of life as compared to mild AR patients. Furthermore, the eosinophil count was significantly higher in IgE-mediated AR patients as compared to non-allergic controls. There were no significant differences in the mean percentages and absolute counts of CD4+ T cell subsets between non-allergic controls and IgE-mediated AR patients. However, significant reduction in the mean percentage (p = 0.0287) and absolute count (p = 0.0298) of CD4+ TEMRA cells were found in IgE-mediated moderate-severe AR patients as compared to IgE-mediated mild AR patients and 14/25 (56.0%) IgE-mediated moderate-severe AR patients had persistent symptoms. In conclusion, the mean percentage and absolute count of CD4+ CD45RA+ CCR7- TEMRA cells were siginificantly reduced in IgE-mediated moderate-severe AR patients as compared to IgE-mediated mild AR patients in our population of AR patients predominantly sensitized to HDMs.